PRODUKTIVITAS DAN NILAI KESETARAAN LAHAN SISTEM TUMPANG SARI HORTIKULTURA DI DATARAN TINGGI MALINO, KABUPATEN GOWA - yusmiaty sabang (Innofarm : Jurnal Inovasi Petanian, 2025)
The application of intercropping systems in the Malino highlands plays an important role in increasing community land productivity, as well as increasing economic value and improving the efficiency of space and time use. The concept of land equivalence ratio (LER) is highly considered in every horticultural planting pattern, because the yield requirements of monoculture will be very different from the intercropping system, where the yield proportion will be more profitable for farmers. The purpose of this study was to analyze land productivity and land equivalence ratio (LER) in the Malino highlands in relation to the intercropping system. This study was conducted on land that applied intercropping patterns, namely leeks-potatoes, leeks-carrots, and leeks-cabbage. The research method was quantitative descriptive through a questionnaire survey and focus group discussion (FGD) with a sample of 30 people selected purposively. The results showed that intercropping patterns yielded excellent production results for each vegetable crop, and the land equality ratio (LER) was > 0.1, meaning that intercropping was more efficient in land use compared to monoculture systems. Keywords : Productivity, Land Equivalency Ratio (LER), Intercropping, Horticulture, Highlands